Development of Smart Villages through Electronic Population Census in Kalimati Village, Jatibarang District - Sumardiono, Sumardiono (Universitas Wiralodra, 2024)
Kalimati Village is one of the villages in Jatibarang District, Indramayu Regency, West Java Province. Most of the residents work as farm laborer’s, who need attention in Information Technology assistance so that residents understand the formation of a smart village. To form a smart village, there are problems that occur, namely economic, educational, and social. The research was carried out using the Action Research method and the prototype system development model. By looking at the problems above, we get a population of 80% farm laborers and 30% random sample as respondents. The results of this study are in the form of data analysis that will be used for the development of a system with a multi-access-based prototype model that focuses on the economic census of the population towards a zero poverty society.